Poisson of bedding mortar under multi-axial stress conditions - Mohamad, Gihad (2012)
The main goal of this work is the understanding of triaxial compression capacity of bedding mortar. It was observed by the experimental tests that the behavior of the stress and strain response is highly nonlinear and depends on the increase of lateral stress. In all studies presented here, the ultimate strength envelope of triaxial mortar can be represented by a linear function with similar angular coefficients. It was observed a significant reduction in the Poisson ratio of mortar with increasing confined stress. This decrease is apparently exponential for mortars types 1:1:6 and 1:2:9 (proportion on volume of cement:lime:sand) and linear for mortars type 1:0.25:3 and 1:0.5:4.5. A simple model is proposed to represent modification of the Poisson ratio throughout the normalized stress range.